Climatology and annual cycle of global ocean dissolved oxygen represented by multiple observational gridded products - Juan Du; Lijing Cheng; Takamitsu Ito; Hernan E. Garcia; Zhankun Wang; Jonathan D. Sharp; Christopher J. Roach; Shoshiro Minobe; Yuntao Zhou; Bin Lu; Gian Giacomo Navarra; Seth M. Bushinsky (Ocean Science, 2026)
Ocean dissolved oxygen (O2) is an essential climate variable crucial for sustaining the marine life; thus, changes of O2 at various spatiotemporal scales should be quantified and understood. Here, we study the climatology and annual cycle of O2 at regional to global scales using eight available gridded observational products. These datasets are generated by different groups using different primary data selection, quality control, bias correction, and interpolation methods, including statistical and machine-learning-based mapping methods. A common set of metrics was collaboratively developed by the community of the Gridded Observational Dataset Intercomparison Project-Dissolved Oxygen (GODIP-DO) to facilitate the inter-comparison. We find that global mean O2 profiles are consistent among all products (±3 µmol kg−1), with the well-established decrease from high surface values to a minimum ∼ 1000 m, and subsequent increase to higher O2 at depth, although local differences could reach ±25 µmol kg−1 (0–1000 m). The hemispheric O2 annual cycle correlates strongly with ocean temperature changes, suggesting the key driver of temperature for the O2 annual cycle. However, there is substantial variation in the global mean 0–100 m O2 annual cycle, the magnitude ranges from −1 to 0.8 µmol kg−1, with a standard deviation of the datasets of ∼ 0.3 µmol kg−1. Average oxygen minimum zones (OMZ) volume among the products is 80.92 × 106 km3 (±1.95 %) for a 60 µmol kg−1 threshold and 152.00 × 106 km3 (±1.72 %) for a 90 µmol kg−1 threshold. Our results help to depict and understand the spread among the available O2 gridded datasets.

Rethinking land-use Strategies: A multi-objective analysis of combined sparing and sharing approaches applied across great britain - Imane El Fartassi; Ryan T. Sharp; Victoria A. Bell; Andrew P. Whitmore; Helen Metcalfe; Nathan Missault; John Redhead; David M. Cooper; Jonathan Storkey; Helen Davies; Theo Jackson; Kevin Coleman; et al. (Journal of Environmental Management, 2026)

Assimilatory processes dominate diel inorganic nitrogen cycling in a shallow open-water constructed wetland - Richard L. Smith; Ariel P. Reed; Deborah A. Repert; Craig R. Tobias; Jonathan O. Sharp (Science of The Total Environment, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Random and systematic uncertainty in ship‐based seawater carbonate chemistry observations - Brendan R. Carter; Jonathan D. Sharp; Maribel I. García‐Ibáñez; Ryan J. Woosley; Michael B. Fong; Marta Álvarez; Leticia Barbero; Simon L. Clegg; Regina Easley; Andrea J. Fassbender; Xinyu Li; Katelyn M. Schockman; et al. (Limnology and Oceanography, 2024)
Seawater carbonate chemistry observations are increasingly necessary to study a broad array of oceanographic challenges such as ocean acidification, carbon inventory tracking, and assessment of marine carbon dioxide removal strategies. The uncertainty in a seawater carbonate chemistry observation comes from unknown random variations and systematic offsets. Here, we estimate the magnitudes of these random and systematic components of uncertainty for the discrete open‐ocean carbonate chemistry measurements in the Global Ocean Data Analysis Project 2022 update (GLODAPv2.2022). We use both an uncertainty propagation approach and a carbonate chemistry measurement “inter‐consistency” approach that quantifies the disagreement between measured carbonate chemistry variables and calculations of the same variables from other carbonate chemistry measurements. Our inter‐consistency analysis reveals that the seawater carbonate chemistry measurement community has collected and released data with a random uncertainty that averages about 1.7 times the uncertainty estimated by propagating the desired “climate‐quality” random uncertainties. However, we obtain differing random uncertainty estimates for subsets of the available data, with some subsets seemingly meeting the climate‐quality criteria. We find that seawater pH measurements on the total scale do not meet the climate‐quality criteria, though the inter‐consistency of these measurements improves (by 38%) when limited to the subset of measurements made using purified indicator dyes. We show that GLODAPv2 adjustments improve inter‐consistency for some subsets of the measurements while worsening it for others. Finally, we provide general guidance for quantifying the random uncertainty that applies for common combinations of measured and calculated values.

Geological and anthropogenic contributions of metal(loid)s in the artisanal and small-scale mining-impacted Ocoña watershed of Arequipa, Peru - Isaac J.P. Simon; Katharina Pfaff; Alexis Navarre-Sitchler; Jorge Crespo; Elizabeth Holley; Gary Vanzin; Madeleine N. Guillen Gomez; Sergio Ticona-Corrales; Jonathan O. Sharp (Applied Geochemistry, 2024)

Photosynthetic pretreatment increases membrane-based rejection of boron and arsenic - Weishi Wang; Colin Wilson Root; Henry F. Peel; Maximilian Garza; Nicholas Gidley; Giuliana Romero-Mariscal; Lino Morales-Paredes; Armando Arenazas-Rodríguez; Juana Ticona-Quea; Johan Vanneste; Gary F. Vanzin; Jonathan O. Sharp (Water Research, 2024)

Uncertainty sources for measurable ocean carbonate chemistry variables - Brendan R. Carter; Jonathan D. Sharp; Andrew G. Dickson; Marta Álvarez; Michael B. Fong; Maribel I. García‐Ibáñez; Ryan J. Woosley; Yuichiro Takeshita; Leticia Barbero; Robert H. Byrne; Wei‐Jun Cai; Melissa Chierici; et al. (Limnology and Oceanography, 2024)
The ocean carbonate system is critical to monitor because it plays a major role in regulating Earth's climate and marine ecosystems. It is monitored using a variety of measurements, and it is commonly understood that all components of seawater carbonate chemistry can be calculated when at least two carbonate system variables are measured. However, several recent studies have highlighted systematic discrepancies between calculated and directly measured carbonate chemistry variables and these discrepancies have large implications for efforts to measure and quantify the changing ocean carbon cycle. Given this, the Ocean Carbonate System Intercomparison Forum (OCSIF) was formed as a working group through the Ocean Carbon and Biogeochemistry program to coordinate and recommend research to quantify and/or reduce uncertainties and disagreements in measurable seawater carbonate system measurements and calculations, identify unknown or overlooked sources of these uncertainties, and provide recommendations for making progress on community efforts despite these uncertainties. With this paper we aim to (1) summarize recent progress toward quantifying and reducing carbonate system uncertainties; (2) advocate for research to further reduce and better quantify carbonate system measurement uncertainties; (3) present a small amount of new data, metadata, and analysis related to uncertainties in carbonate system measurements; and (4) restate and explain the rationales behind several OCSIF recommendations. We focus on open ocean carbonate chemistry, and caution that the considerations we discuss become further complicated in coastal, estuarine, and sedimentary environments.

Transitional dynamics from mercury to cyanide-based processing in artisanal and small-scale gold mining: Social, economic, geochemical, and environmental considerations - Aaron Malone; Linda Figueroa; Weishi Wang; Nicole M. Smith; James F. Ranville; David C. Vuono; Francisco D. Alejo Zapata; Lino Morales Paredes; Jonathan O. Sharp; Christopher Bellona (Science of The Total Environment, 2023)

Heavy metal removal by the photosynthetic microbial biomat found within shallow unit process open water constructed wetlands - Zhaoxun Yang; Sarah M. Acker; Adam R. Brady; Armando Arenazas Rodríguez; Lino Morales Paredes; Juana Ticona; Giuliana Romero Mariscal; Gary F. Vanzin; James F. Ranville; Jonathan O. Sharp (Science of The Total Environment, 2023)

Surface displacement expression of progressive failure in a sensitive clay landslide observed with long-term UAV monitoring - Michael J. Bentley; Jonathan M. Foster; Joshua J. Potvin; George Bevan; James Sharp; David J. Woeller; W. Andy Take (Landslides, 2023)

PMEL’s Contribution to Observing and Analyzing Decadal Global Ocean Changes Through Sustained Repeat Hydrography - Zachary Erickson; Brendan Carter; Richard Feely; Gregory Johnson; Jonathan Sharp; Rolf Sonnerup (Oceanography, 2023)
The ocean is warming, acidifying, and losing oxygen. The Global Ocean Ship-based Hydrographic Investigations Program (GO-SHIP) carries out repeat hydrographic surveys along specified transects throughout all ocean basins to allow accurate and precise quantification of changes in variables such as temperature, salinity, carbon, oxygen, nutrients, velocity, and anthropogenic tracers, and uses these observations to understand ventilation patterns, deoxygenation, heat uptake, ocean carbon content, and changes in circulation. GO-SHIP provides global, full-depth, gold-standard data for model validation and calibration of autonomous sensors, including Argo. The Pacific Marine Environmental Laboratory, through sustained funding from NOAA, has developed methods to measure several of the variables routinely sampled through GO-SHIP and is a core contributor to these repeat hydrographic cruises.

Use of multiple endpoints to assess the impact of captivity on gut flora diversity in Long Island Sound Fundulus heteroclitus - Joseph P. Battaglia; Christian M. Kearney; Kirsten Guerette; Jordan Corbishley; Emily Sanchez; Brennah Kent; Hanna Storie; Emma Sharp; Shane Martin; Matthew Saberito; Jonathan D. Blake; Richard S. Feinn; et al. (Environmental Biology of Fishes, 2022)

Best Practice Data Standards for Discrete Chemical Oceanographic Observations - Li-Qing Jiang; Denis Pierrot; Rik Wanninkhof; Richard A. Feely; Bronte Tilbrook; Simone Alin; Leticia Barbero; Robert H. Byrne; Brendan R. Carter; Andrew G. Dickson; Jean-Pierre Gattuso; Dana Greeley; et al. (Frontiers in Marine Science, 2022)
Effective data management plays a key role in oceanographic research as cruise-based data, collected from different laboratories and expeditions, are commonly compiled to investigate regional to global oceanographic processes. Here we describe new and updated best practice data standards for discrete chemical oceanographic observations, specifically those dealing with column header abbreviations, quality control flags, missing value indicators, and standardized calculation of certain properties. These data standards have been developed with the goals of improving the current practices of the scientific community and promoting their international usage. These guidelines are intended to standardize data files for data sharing and submission into permanent archives. They will facilitate future quality control and synthesis efforts and lead to better data interpretation. In turn, this will promote research in ocean biogeochemistry, such as studies of carbon cycling and ocean acidification, on regional to global scales. These best practice standards are not mandatory. Agencies, institutes, universities, or research vessels can continue using different data standards if it is important for them to maintain historical consistency. However, it is hoped that they will be adopted as widely as possible to facilitate consistency and to achieve the goals stated above.

Vortioxetine reverses medial prefrontal cortex-mediated cognitive deficits in male rats induced by castration as a model of androgen deprivation therapy for prostate cancer - Alexandra M. Sharp; Suphada Lertphinyowong; Samantha S. Yee; Denisse Paredes; Jonathan Gelfond; Teresa L. Johnson-Pais; Robin J. Leach; Michael Liss; April L. Risinger; Anna C. Sullivan; Ian M. Thompson; David A. Morilak (Psychopharmacology, 2019)

Ertapenem for osteoarticular infections in obese patients: a pharmacokinetic study of plasma and bone concentrations - Jonathan Chambers; Madhu Page-Sharp; Sam Salman; John Dyer; Timothy M. E. Davis; Kevin T. Batty; Laurens Manning (European Journal of Clinical Pharmacology, 2019)

The Regulation of Monoamine Oxidase A Gene Expression by Distinct Variable Number Tandem Repeats - Maurizio Manca; Veridiana Pessoa; Ana Illera Lopez; Patrick T. Harrison; Fabio Miyajima; Helen Sharp; Andrew Pickles; Jonathan Hill; Chris Murgatroyd; Vivien J. Bubb; John P. Quinn (Journal of Molecular Neuroscience, 2018)

Erratum to: Impact of Bi-Axial Shear on Atherogenic Gene Expression by Endothelial Cells - Amlan Chakraborty; Sutirtha Chakraborty; Venkatakrishna R. Jala; Jonathan M. Thomas; M. Keith Sharp; R. Eric Berson; Bodduluri Haribabu (Annals of Biomedical Engineering, 2016)

Impact of Bi-Axial Shear on Atherogenic Gene Expression by Endothelial Cells - Amlan Chakraborty; Sutirtha Chakraborty; Venkatakrishna R. Jala; Jonathan M. Thomas; M. Keith Sharp; R. Eric Berson; Bodduluri Haribabu (Annals of Biomedical Engineering, 2016)

Clinical and genomic evaluation of 201 patients with Phelan–McDermid syndrome - Sara M. Sarasua; Luigi Boccuto; Julia L. Sharp; Alka Dwivedi; Chin-Fu Chen; Jonathan D. Rollins; R. Curtis Rogers; Katy Phelan; Barbara R. DuPont (Human Genetics, 2014)

Anomalous Biogeochemical Response to a Flooding Event in the Delaware Estuary: A Possible Typology Shift Due to Climate Change - Yoana G. Voynova; Jonathan H. Sharp (Estuaries and Coasts, 2012)

BOOK REVIEW | Escape from the Ivory Tower: A Guide to Making Your Science Matter - Jonathan Sharp (Oceanography, 2011)

Shrub-Steppe Early Succession Following Juniper Cutting and Prescribed Fire - Jonathan D. Bates; Kirk W. Davies; Robert N. Sharp (Environmental Management, 2011)

Estuarine oxygen dynamics: What can we learn about hypoxia from long‐time records in the Delaware Estuary? - Jonathan H. Sharp (Limnology and Oceanography, 2010)
Hypoxia and anoxia occurred in the upper Delaware Estuary throughout much of the 20th century and diminished over the past several decades. I reviewed 30 yr of data from my laboratory's research efforts, 40 yr of consistent monitoring data from a multistate agency, results from inconsistent data collection from the past century, and anecdotal information to construct a long‐time picture of the decline and increase of dissolved oxygen concentrations (DO) in the urban region of the estuary. The primary cause of the DO decline appeared to be inputs or allochthonous materials from urban sources (reduced nitrogen and carbon). In spite of extremely high nutrient concentrations, excess algal production did not influence DO anywhere along the tidal freshwater stretch or the saline portion of the well‐mixed Delaware Estuary; and it does not have an influence today. The nutrient loading to the Delaware Estuary is very high, yet the typical signs of eutrophication are not obvious. Based on a model of apparent oxygen utilization, the Delaware Bay apparently had higher primary production 50 yr ago, a time when nutrient concentrations were as high or higher than today, shellfish and finfish production were apparently also higher, and DO was close to saturation. This analysis is offered as guidance in assessing and managing estuarine eutrophication, which is too often considered narrowly to be the result of inadvertent overfertilization by nutrients or a single nutrient element.

BOOK REVIEW | Don’t Be Such a Scientist: Talking Substance In An Age of Style - Jonathan Sharp (Oceanography, 2009)

A Biogeochemical View of Estuarine Eutrophication: Seasonal and Spatial Trends and Correlations in the Delaware Estuary - Jonathan H. Sharp; Kohei Yoshiyama; Alexander E. Parker; Matthew C. Schwartz; Susan E. Curless; Allison Y. Beauregard; Justin E. Ossolinski; Allen R. Davis (Estuaries and Coasts, 2009)

Phytoplankton response to nutrient enrichment in an urbanized estuary: Apparent inhibition of primary production by overeutrophication - Kohei Yoshiyama; Jonathan H. Sharp (Limnology and Oceanography, 2006)
Phytoplankton response to nutrients was examined with a 26‐yr database from the Delaware Estuary. Biomassnormalized primary production did not increase linearly with increasing nutrient concentrations and instead showed saturation at comparatively low nutrient concentrations and decreased at high concentrations. To separate the effects of light availability and temperature on primary production from those of other environmental variables, we developed an empirical model of areal primary production. The model equation was obtained for the entire dataset and the effect of the residual variables was expressed as correction factors of observed primary production to the model estimates. The model accounted for 67% of variability of observed primary production overall, indicating that production of the estuary was mainly controlled by light availability and temperature. In contrast, a similar model applied to a Chesapeake Bay database had shown a poorer fit, indicating consistent light limitation in the Delaware Estuary and varying strengths of light and nutrient limitation in the Chesapeake Bay. The relationships between nutrients and correction factors for the Delaware Estuary showed that the model underestimates primary production at low and mid nutrient concentrations and overestimates it at high concentrations. The model fit and correction factors for five regions of the estuary indicate a high‐nutrient, low‐growth situation in the Delaware Estuary because of varying influences of light limitation, proportions of nutrients, and probably toxic contaminants in areas with large anthropogenic inputs—including high nutrients.

In situ feeding and element removal in the symbiont‐bearing sponge Theonella swinhoei : Bulk DOC is the major source for carbon - Gitai Yahel; Jonathan H. Sharp; Dominique Marie; Clivia Häse2; Amatzia Genin (Limnology and Oceanography, 2003)
The vast majority of organic matter in the world ocean is found in the dissolved pool. However, no evidence has been demonstrated for direct uptake of bulk dissolved organic matter (DOM) by organisms other than bacteria and some invertebrate larvae. The total organic carbon (TOC) is 10—30% higher in coral reefs than in adjacent open waters. The dissolved organic carbon (DOC) accounts for >90% of the TOC. Using a new in situ technique for clean sampling of the seawater inhaled and exhaled by benthic suspension feeders, we measured directly the removal of DOC in the symbiont‐bearing reef sponge Theonella swinhoei . The sponge removed up to 26% (± SD: 12% ± 8%) of the TOC (dissolved and particulate) from the water it filtered during a single passage through its filtration system. Most of the carbon gained by the sponge was from the dissolved pool (10 ± 7 µmol C L −1 ), an order of magnitude greater than the carbon gained from the total living cells (phytoplankton and bacteria) the sponge removed (2 ± 1 µmol C L ‐ ). In T. swinhoei , over two‐thirds of the sponge biomass consists of symbiotic bacteria, which likely play an important role in DOC uptake. Our findings indicate that the role of DOC in metazoan nutrition and the role of metazoans in DOC cycling may have been grossly underestimated.

Self-administration in rats allowed unlimited access to nicotine - James D. Valentine; Jonathan S. Hokanson; Shannon G. Matta; B. M. Sharp (Psychopharmacology, 1997)

DOC Intercalibration to End Soon - Jonathan Sharp (Oceanography, 1995)

Diverse Career Possibilities and a Broad Oceanography Curriculum - Jonathan Sharp (Oceanography, 1995)

The Dissolved Organic Carbon Controversy: An Update - Jonathan Sharp (Oceanography, 1993)